Photosynthesis: carbon assimilation - Leegood, Richard (Henry Stewart Talks, 2007)
The Benson-Calvin cycle, Synthesis of starch and sucrose, Rubisco and its regulation, Photorespiration, CO2- concentrating mechanisms, C4 photosynthesis, Crassulacean acid metabolism